THE PRACTICAL AND ETHICAL CHALLENGES OF CONDUCTING RESEARCH WITH CHILDREN AND ADOLESCENTS - Bundovska Smiljana; Uljarević Mirko (My University, 2009)
Due to its noninvasive nature, good spatial resolution and other advantages functional magnetic resonance imaging (fMRI) has become a tool of choice for investigating the brain mechanisms underlying psychological phenomena. Functional MRI studies have elicted substantial media coverage and this has led to increased public interest in neuroimaging. Having in mind enormous potential of this method as well as potential risks it is of crucial importance to be aware of ethical and practical challenges when conducting fMRI research, especially with children and adolescents. In this essay we selectively review issues regarding informed consent and child’s capacity to withdraw from the study, importance of incidental findings and the problem of motion during image acquisition. Strategies how to deal with those problems are also addressed.
Keywords: functional magnetic resonance imaging; informed consent; incidental findings; motion